1998
DOI: 10.2307/2446305
|View full text |Cite
|
Sign up to set email alerts
|

Genome size and numerical polymorphism for the B chromosome in races of maize (Zea mays ssp. mays, Poaceae)

Abstract: Twenty-one native populations (1120 individuals) of maize from Northern Argentina were studied. These populations, which belong to 13 native races, were cultivated at different altitudes (80-3620 m). Nineteen of the populations analyzed showed B chromosome (Bs) numerical polymorphism. The frequency of individuals with Bs varied from 0 to 94%. The number of Bs per plant varied from 0 to 8 Bs, with the predominant doses being 0, 1, 2, and 3. Those populations with varying number of Bs showed a positive and stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
69
1
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 22 publications
11
69
1
5
Order By: Relevance
“…The cytogenetic studies conducted by Rosato et al (1998) and Poggio et al (1998) in 21 native populations from northwestern Argentina revealed a negative correlation between the mean number of B's per plant and the number of heterochromatic bands and a positive correlation between the mean number of B's per plant and altitude. According to these authors, B's would be tolerated at high frequencies in those populations with lower numbers of heterochromatic bands, so as to maintain a relatively constant amount of nuclear DNA or an ''optimal'' nucleotype (sensu Bennett 1987).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The cytogenetic studies conducted by Rosato et al (1998) and Poggio et al (1998) in 21 native populations from northwestern Argentina revealed a negative correlation between the mean number of B's per plant and the number of heterochromatic bands and a positive correlation between the mean number of B's per plant and altitude. According to these authors, B's would be tolerated at high frequencies in those populations with lower numbers of heterochromatic bands, so as to maintain a relatively constant amount of nuclear DNA or an ''optimal'' nucleotype (sensu Bennett 1987).…”
mentioning
confidence: 97%
“…mays L.). Numerical polymorphisms have been described in a large number of maize landraces (Mcclintock et al 1981;Chiavarino et al 1995;Naranjo et al 1995;Rosato et al 1998), with differences in the number of B's being one of the main factors contributing to intraspecific genome-size variation. Although several accumulation mechanisms have been reported for maize B chromosomes (Roman 1947(Roman ,1948Carlson and Chou 1981;Carlson and Roseman 1992), the significance of the distinctive patterns of occurrence of these supernumerary elements in different native populations still remains unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Las variaciones en el tamaño del genoma se deberían fundamentalmente a variaciones en el contenido de heterocromatina de los cromosomas, sobre todo de aquellas zonas que tienen secuencias repetidas en tándem (Flavel, 1986;Price 1988;Tito et al 1991;Rosato et al, 1998). En cambio para San Miguel et al, 1996Miguel et al, , 1998Okagaki y Phillips, 2004, en genomas complejos como los de los eucariotas, aún no se conoce con exactitud cuál es la organización relativa de los genes y la función del DNA repetido.…”
Section: Estudio Genómico De Zeaunclassified